Prognostic potential of inflammatory markers in chronic kidney disease patients combined with acute myocardial infarction - Dang, Peizhu; Li, Bohan; Li, Yongxin (Frontiers in Cardiovascular Medicine, 2024)
BackgroundInflammation significantly impacts chronic kidney disease (CKD) and acute myocardial infarction (AMI). This study investigates the prognostic value of inflammatory markers in predicting outcomes for CKD patients with AMI.MethodsWe enrolled patients diagnosed with CKD concomitant with AMI, choosing five inflammatory markers related to both diseases. Patients were categorized into elevated inflammatory markers group and control group based on inflammatory markers cut-off values for predicting in-hospital major adverse cardiac and cerebrovascular events (MACCE). Using univariate and multivariate logistic regression, we identified inflammation-related risk factors for MACCE. We adjusted covariates stepwise to explore the relationship between independent risk factors and adverse outcomes. We also evaluated the predictive value of these markers for MACCE by receiver operating characteristic (ROC) curves.ResultsIn the multivariate logistic regression analysis, higher levels of neutrophil-to-lymphocyte ratio (NLR), and platelet to lymphocyte ratio (PLR) significantly increased risk of MACCE (all P < 0.05). After adjusting above two indicators, NLR was independently associated with in-hospital MACCE in CKD patients with AMI (OR = 10.764, 95% CI: 1.887–61.406, P = 0.007). Furthermore, compared to other inflammatory markers, NLR had the highest predictive value for MACCE in patients with AMI and CKD [Area Under the Curve (AUC): 0.748, 95% Confidence Interval (CI): 0.634–0.861, P < 0.001].ConclusionIn CKD patients combined with AMI, elevated levels of inflammation markers could increase the risk of MACCE. NLR may provide superior predictive value compared to other markers.